2022
DOI: 10.2478/arsa-2022-0002
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Artificial Neural Network and the Optimal GNSS Satellites’ Configuration for Improving GNSS Positioning Techniques (A Case Study in Egypt)

Abstract: Nowadays, theglobal navigation satellite system (GNSS) positioning techniques based on the International GNSS Service (IGS) products are extensively used for various precise applications. However, specific conditions such as the dual-frequency observations and the final IGS products are required. Consequently, the absence of the final IGS data and using single-frequency observations will degrade these techniques’ accuracy. In this paper, two algorithms through two separated stages are formulated for improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Consequently, the number of initializations was set at 100; this iterated automatically. One hidden layer with ten neurons was selected, according to the recommendation of Alemam, Yong, and Mohammed (2022). During the development of this ANN algorithm, the results indicated that the linear activation function (pure-line), in the hidden and output layers, is suitable for this network and data compared to the other activation functions.…”
Section: Ann Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the number of initializations was set at 100; this iterated automatically. One hidden layer with ten neurons was selected, according to the recommendation of Alemam, Yong, and Mohammed (2022). During the development of this ANN algorithm, the results indicated that the linear activation function (pure-line), in the hidden and output layers, is suitable for this network and data compared to the other activation functions.…”
Section: Ann Techniquementioning
confidence: 99%
“…Overall, the ANN reached the best results with additional GNSS points at the border. This is because the ANN simulation performs best with a high volume of data (Alemam et al 2022). Therefore, the ANN is preferred as its cost-effective.…”
Section: Slopes and Aspectsmentioning
confidence: 99%
“…In response to these challenges, researchers have begun to explore alternative approaches to geodetic data processing, with soft computing techniques emerging as a promising option. Soft computing is an interdisciplinary field that encompasses several computational methodologies, including artificial neural networks (ANNs) [3][4][5], fuzzy logic, and evolutionary algorithms (EAs). These techniques are characterized by their ability to handle imprecise, uncertain, and incomplete information, making them well-suited for addressing the challenges associated with geodetic data processing.…”
Section: Introductionmentioning
confidence: 99%